PROBLEM-BASED LEARNING AND OUTDOOR ACTIVITIES VISITING STUDENTS AT BOGOR REGIONAL PLANNING AND DEVELOPMENT AGENCY - Wicaksono, Arief; Badri, Lusi Nurbaiti; Savitri, Ratu Desy; Dewi, Irma Arlini; Azzam, Muhammad (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
This article develops a learning model for the visiting students in Bogor Municipality Regional Planning and Development Agency (BAPPEDA). The proposed learning model is developed from a combined Problem-based Learning (PBL) and Outdoor Activity. Four students from a senior high school visited Bappeda from January 2nd 2023 until January 13th 2023. During their visit in Bappeda, students performed series of activities which include document analysis, discussion to decide study location, GIS (Geographic Information System) practice learning, field surveys, and final presentation. From these activities, a learning model was developed according to the PBL and oudoor learning principles.  Three major outcomes are generated from this combined learning model namely, students are able to map the Kampung Lauk using GIS sofware, students can prepare a simple questionnaire to inquire Bappeda employees’ perception about Kampung Lauk and distribute it, and students can identify problems relate to the development of Kampung Lauk and perform final presentation to offer recommendations.